FUNCTIONAL DYNAMICS OF VOCATIVES IN RHETORICAL DISCOURSE - Seytzhanov Jetkerbay Elubaevich (Bright Mind Publishing, 2025)
This article investigates the communicative and functional roles of vocatives in rhetorical discourse, moving beyond their traditional attention‐calling function to reveal a spectrum of pragmatic effects. Drawing on Jakobson’s (1960) framework of language functions, we reinterpret vocatives as multifunctional devices that manage speaker–hearer relationships, modulate emotional intensity, and reinforce persuasive intent (Jakobson, 1960). Empirical studies in Slavic and Romance contexts (Glušac & Mikić Čolić, 2018; Noel & Sonnenhauser, 2020) are contrasted with research on Uzbek appellatives (Islomova, 2019; Khakimova, 2021) to identify both universal patterns and language‐specific manifestations. Our analysis demonstrates how vocatives operate as discourse markers, solidarity signals, and evaluative tools, thus enriching rhetorical strategies in political speeches, media texts, and literary narratives. By integrating functional‐pragmatic and discourse‐analytic perspectives, the study offers a comprehensive account of vocative use and lays groundwork for further cross‐linguistic investigation.
Keywords: Vocatives, rhetorical discourse, communicative function, functional pragmatics, Uzbek appellatives, discourse markers, solidarity signals, persuasive strategies.